CORRELATION OF LYMPHOCYTE-MONOCYTE RATIO AND MORTALITY OF COVID-19 INTENSIVE CARE UNIT PATIENTS: PRELIMINARY STUDY - Naufal, Muhammad Fadhil; Susanti, Ade; Quzwain, Fairuz (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2023)
Background: The world faces a pandemic caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARSCov-2). Because of the limitations as a developing country, Indonesia needs to do its activities efficiently in time,money, and human resource. This research aims to accurately determine a concrete mortality predictor to predictthe patients' mortality. One of the mortality predictors is the lymphocyte-monocyte ratio (LMR).Method: This research is observational analytic research using a cross-sectional study method. Data obtainedfrom the Medical Record & Casemix Room of RSUD Raden Mattaher.Results: Out of 115 samples, most patients were male (65 patients). The patients' age group was mainly youngerthan 65 (79%). The most common comorbidity was diabetes mellitus (43 patients). The correlation between LMRand mortality rate to be weak with the following results: Pearson coefficient(p=0.045), gamma coefficient (P=0.325),Somers' D test (P=0.167), odds ratio (1.833), AUC (58%), specificity (58%), sensitivity (56%), and intersection point(1,79).Conclusions: There is a weak correlation between LMR and the mortality rate of COVID-19 patients in RSUDRaden Mattaher.Keywords: Characteristics of COVID-19 patients, comorbidity of COVID-19 patients, LMR (Lymphocyte-monocyteratio), a mortality rate of COVID-19 patients.